Biodecomposition of Phenanthrene and Pyrene by a Genetically Engineered Escherichia coli - Ahankoub, Maryam; Mardani, Gashtasb; Ghasemi-Dehkordi, Payam; Mehri-Ghahfarrokhi, Ameneh; Doosti, Abbas; Jami, Mohammad-Saeid; Allahbakhshian-Farsani, Mehdi; Saffari-Chaleshtori, Javad; Rahimi-Madiseh, Mohammad (Recent Patents on Biotechnology, 2020)
Background: Genetically engineered microorganisms (GEMs) can be used for bioremediation of the biological pollutants into nonhazardous or less-hazardous substances, at lower cost. Polycyclic aromatic hydrocarbons (PAHs) are one of these contaminants that associated with a risk of human cancer development. Genetically engineered E. coli that encoded catechol 2,3- dioxygenase (C230) was created and investigated its ability to biodecomposition of phenanthrene and pyrene in spiked soil using high-performance liquid chromatography (HPLC) measurement. We revised patents documents relating to the use of GEMs for bioremediation. This approach have already been done in others studies although using other genes codifying for same catechol degradation approach. Objective: In this study, we investigated biodecomposition of phenanthrene and pyrene by a genetically engineered Escherichia coli. Methods: Briefly, following the cloning of C230 gene (nahH) into pUC18 vector and transformation into E. coli Top10F, the complementary tests, including catalase, oxidase and PCR were used as on isolated bacteria from spiked soil. Results: The results of HPLC measurement showed that in spiked soil containing engineered E. coli, biodegradation of phenanthrene and pyrene comparing to autoclaved soil that inoculated by wild type of E. coli and normal soil group with natural microbial flora, were statistically significant (p<0.05). Moreover, catalase test was positive while the oxidase tests were negative. Conclusion: These findings indicated that genetically manipulated E. coli can provide an effective clean-up process on PAH compounds and it is useful for bioremediation of environmental pollution with petrochemical products.
Keywords: PAH